TEKNOLOGI REMOTE SENSING (PENGINDERAAN JARAK JAUH) DALAM PENYELESAIAN SENGKETA BLOK AMBALAT - Evert Maximiliaan Tentua (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
The publication of the Malaysia Territorial Map 1979 make a problems of law between Malaysia states with Indonesia state especially the claim of Malaysia to block Ambalat, because based on international custom Malaysia state ought to before making the Malaysia Territorial Map 1979 shall beforehand makes an agreement about sea delimitation with based on multilateral or bilateral agreement of neighbour inter-states and not unilaterally ( as of party) like the one has been determined in United Nations Convention on the Law Of the Sea 1982, and finalize problems of the law is Indonesia state must can assure in any international forums and also international court that is without just is supplied with law bases which can be applied but having to has also accurate supporter data, and for to get the accurate data, the Indonesia state needs to apply of the technology remote sensing by satellite.